The causality between gut microbiota and endometriosis: a bidirectional Mendelian randomization study - Yang, Hua (Frontiers in Medicine, 2024)
Background: Observational studies and animal experiments had suggested a potential relationship between gut microbiota abundance and pathogenesis of endometriosis(EMs), but the relevance of this relationship remains to be clarified.We perform a two-sample bidirectional Mendelian randomization (MR) analysis to explore whether there is a causal correlation between the abundance of the gut microbiota and EMs and the direction of causality. Genome-wide association study (GWAS) data ukb-d-N80, finn-b-N14-EM, and MiBinGen were selected. Inverse variance weighted (IVW), weighted median, and MR Egger are selected for causal inference. The Cochran Q test, Egger intercept test, and leave-one-out analysis are performed for sensitivity analyses.In the primary outcome, we find that a higher abundance of class Negativicutes, genus Dialister, genus Enterorhabdus, genus Eubacterium xylanophilum group, genus Methanobrevibacter and order Selenomonadales predict a higher risk of EMs, and a higher abundance of genus Coprococcus and genus Senegalimassilia predict a lower risk of EMs. During verifiable outcomes, we find that a higher abundance of phylum Cyanobacteria, genus Ruminococcaceae UCG002, and genus Coprococcus 3 predict a higher risk of EMs, and a higher abundance of genus Flavonifracto, genus Bifidobacterium, and genus Rikenellaceae RC9 predict a lower risk of EMs. In primary reverse MR analysis, we find that EMs predict a lower abundance of the genus Eubacterium fissicatena group, genus Prevotella7, genus Butyricicoccus, family Lactobacillaceae, and a higher abundance of genus Ruminococcaceae UCG009. In verifiable reverse MR analysis, we find that EMs predict a lower abundance of the genus Ruminococcaceae UCG004 and a higher abundance of the genus Howardella.Our study implies a mutual causality between gut microbiota abundance and the pathogenesis of EMs, which may provide a novel direction for EMs diagnosis, prevention, and treatment, may promote future functional or clinical analysis.